Analisis Pesan Dakwah Moderasi Dalam Novel Kidung Rindu Di Tapal Batas Karya Aguk Irawan Mn. - Rukayah, Siti; Qadaruddin, Muhammad; Haramain, Muhammad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
The development of da'wah in the digital era is inseparable from the problem of society as a target for da'wah and so many media are used as a means of da'wah. One of the means used by many preachers to deliver their da'wah material is through written media and literacy such as novels. The novel is one of the alternative dawah for delivering dawah material to the target of preaching or mad'u, many stories in the novel are promoted as messages of propaganda in the form of film media. This article has a very positive purpose in understanding the contents of da'wah what are the meanings in a story that have elements of nationalism and da'wah by using descriptive qualitative methods, then linking them to interpretations of the Qur'an.